Humor sebagai Bentuk Pelanggaran Maksim Kerja Sama dalam Animasi Saiki Kusuo no Psinan - Eka Triyana (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2019)
This study aims to describe the occurrence of humor based on the cooperative principles theory by Grice (1975) and the theory of incongruity about the use cooperative principle violations in the humor of Saiki Kusuo no Psinan animation. The paradigm of this research is qualitative research with a pragmatic approach. The data source of this research is the Saiki Kusuo no Psinan animation. The data were in the form of 15 utterances containing humor. The utteranceswere then analyzed based on Grice's cooperative principles to look for violations of the cooperative principles. The utterances were also analyzed by using the theory of incongruity to see the humor formed from the utterances of the character. From the results of the sanalysis, it is concluded that humor occurs because of the violation of cooperative principles caused by the incongruent situation. In 15 utterances, there are various violations of the cooperative principles. Those are: 3 maxim of quantity violations, 1 maxim of quality violation, 4 maxim of relevance violations, and 4 maxim of manner violations.In addition, there are also 3 utterances that violated 2 maxims at once, i.e. 1 violation of maxim of quantity and relevance, 1 violation of maxim of quality and quantity, 1 violation of maxim of manner and relevance. These 15 utterances cause an incongruent situation that triggers humor.